2019
DOI: 10.1108/joepp-12-2018-0121
|View full text |Cite
|
Sign up to set email alerts
|

Supporting SMEs’ internationalisation through a deeper understanding of human and technology barriers

Abstract: Purpose The purpose of this paper is to investigate small- and medium-sized enterprises’ (SMEs) internationalisation from an emerging market perspective. It explores and applies human resource management (HRM) processes to small businesses’ internationalisation efforts in order to ascertain the extent to which human- and technology-oriented barriers to internationalisation can be better understood and their processes better managed by SMEs. Design/methodology/approach The data collection and analysis involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 109 publications
0
24
1
1
Order By: Relevance
“…[20] John Mendy's research results highlight the importance of the HRM process in the proper management of human and technological constraints, which are as important as the internationalization of SMEs. [21] Research by Syed Zamberi Ahmad found that SMEs' motives for international expansion are diverse and that SMEs still face many institutional challenges, which prevent them from making a larger contribution. [22] The research conducted by Mohammed Ngoma in this study determined a significant relationship between the dimensions of entrepreneurial orientation (EO) and the internationalization of SMEs.…”
Section: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…[20] John Mendy's research results highlight the importance of the HRM process in the proper management of human and technological constraints, which are as important as the internationalization of SMEs. [21] Research by Syed Zamberi Ahmad found that SMEs' motives for international expansion are diverse and that SMEs still face many institutional challenges, which prevent them from making a larger contribution. [22] The research conducted by Mohammed Ngoma in this study determined a significant relationship between the dimensions of entrepreneurial orientation (EO) and the internationalization of SMEs.…”
Section: Previous Researchmentioning
confidence: 99%
“…It is in line with John Mendy's research that the importance of managing Human Resource Management from the constraints of limited human resources and technology is as important as internationalization. [21]International trade procedures require resources capable of managing this. Most MSMEs in Indonesia, including the Magetan leather handicraft business, do not have this capability, so reaching the international market will be very difficult.…”
Section: Limited Resourcesmentioning
confidence: 99%
“…Hence, different proposals in the literature seek to address the underperformance problem by demystifying the factors that may have led to the current situation (Ndiaye et al, 2018). Other scholars have added their voices onto the impact of HRM and management practices in boosting organisational and individual performance (Schmelter et al, 2010;Mendy and Rahman, 2019). Limited success has been registered in previous studies on how SMEs can resolve the myriad of factors that appear to have contributed to such a problem (Rehman and Anwar, 2019;Chibelushi and Costello, 2009).…”
Section: Introduction and Research Contextmentioning
confidence: 99%
“…what employees see as the actual problem and, more importantly, how they think this could be resolved). Although the paper's findings and its data were collected as part of a longitudinal study between 2004 and 2011, the results bring fresh insights into how to resolve the ongoing SME underperformance problem whilst still contributing to create greater awareness, fresh insights and understanding of performance management issues in SMEs (Sok et al, 2016;Mendy and Rahman, 2019).…”
Section: Introduction and Research Contextmentioning
confidence: 99%
“…Thus, this paper adds to the limited literature relating to the use of PSO and ANN for businesses in developing countries. Developing countries generally tend to have inadequate infrastructure, which could cause additional barriers to business (Mendy and Rahman, 2019;Riahi and Hammami, 2019). Indeed, Mertzanis (2019) pointed out that firms experience financial constraints across developing countries.…”
Section: Introductionmentioning
confidence: 99%